the Spirit of Reformation: the Finality of Biblical Truth as an Educator's Challenge in Teaching Christian Education - Sidharta, Juaniva (Advances In Social Humanities Research, 2025)
The spirit of reformation reminds us of the struggle and sacrifice of the reformers in restoring the truth of the Bible, which is believed to be God's revelation to humanity. The Bible serves as the source, foundation, and highest standard of truth, representing the final authority in all aspects of the lives of believers. Educators play a central role in embodying the spirit of reformation, especially through teaching the five main principles: Sola Scriptura (Scripture as the sole infallible source of truth), Sola Gratia (salvation by God's grace alone), Sola Fide (salvation obtained through faith alone), Solus Christus (Christ alone, as the only Mediator between God and humanity), and Soli Deo Gloria (glory to God alone).  The spirit of reformation, which focuses on the purification of medieval teachings by the reformers, presents a significant challenge for Christian Education (CE) today. Amidst the changes of the times and the influence of modern values, CE academics must return to the core of the spirit of reformation to uphold and teach the church’s faith and the truth of the Bible. In this way, Christian Education can continue to be a means of shaping character and faith based on the truth of God's Word.